2008
DOI: 10.48550/arxiv.0808.3458
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A central limit theorem for the rescaled Lévy area of two-dimensional fractional Brownian motion with Hurst index $H<1/4$

Jeremie Unterberger

Abstract: Let B = (B (1) , B (2) ) be a two-dimensional fractional Brownian motion with Hurst index α ∈ (0, 1/4). Using an analytic approximation B(η) of B introduced in [22], we prove that the rescaled Lévy area process (s, t) → η(1)t 2 (η) converges in law to Wt − Ws where W is a Brownian motion independent from B. The method relies on a very general scheme of analysis of singularities of analytic functions, applied to the moments of finite-dimensional distributions of the Lévy area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2010
2010
2011
2011

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
2
0
1
Order By: Relevance
“…Despite an abstract (non constructive) proof of existence [36], and several recent investigations [51,50,14] yielding a sort of general classification of rough paths in the algebraic sense, this series of papers gives the first construction of a rough path over B for α ≤ 1/4 by means of an explicit sequence of approximations. The barrier at α = 1/4 has been recognized by several authors using different approaches [11,42,47,48], and shown to extend to other models as well [26].…”
Section: Introductionmentioning
confidence: 85%
“…Despite an abstract (non constructive) proof of existence [36], and several recent investigations [51,50,14] yielding a sort of general classification of rough paths in the algebraic sense, this series of papers gives the first construction of a rough path over B for α ≤ 1/4 by means of an explicit sequence of approximations. The barrier at α = 1/4 has been recognized by several authors using different approaches [11,42,47,48], and shown to extend to other models as well [26].…”
Section: Introductionmentioning
confidence: 85%
“…une intégrale itérée d'ordre 2, définie comme limite des intégrales itérées des interpolations linéaires par morceaux des trajectoires, diverge quand α ≤ 1/4. Des travaux ultérieurs reposant sur des méthodes différentes [15,57,65,66] ont confirmé l'existence de cette barrière apparemment infranchissable en α = 1/4. Et pourtant, la théorie des chemins rugueux * (ou rough paths), une théorie d'intégration adaptée aux chemins irréguliers, introduite par T. Lyons à la fin des années 90 [46,47] et devenue un outil essentiel en calcul stochastique [46,47,33,44,45,25], prédit -malheureusement par des arguments géométriques non constructifs -l'existence d'approximations C 1 par morceaux, autres que l'interpolation linéaire par morceaux, dont les intégrales itérées de tous ordres convergent vers des quantités finies s'interprétant comme substituts d'intégrales itérées du brownien fractionnaire -en termes plus géométriques, comme chemin rugueux au-dessus du brownien -.…”
Section: Introductionunclassified
“…called Lévy area. The corresponding Stratonovich integral, obtained as a limit either by linear interpolation or by more refined Gaussian approximations [11,51,58,59], has been shown to diverge as soon as α ≤ 1/4. This seemingly no-go theorem, although clear and derived by straightforward computations that we reproduce in short in section 1, appears to be a puzzle when put in front of the results of rough path theory [43,44,28,39,40,20].…”
Section: Introductionmentioning
confidence: 99%